Emerging lessons from the commissioning and delivery of a gambling treatment service. (July 2021) - Woodall, J.; Freeman, C.
Abstract: Objectives: Gambling is a public health concern, given the multiplicity of harms for individuals, families and communities. This article reports on the commissioning and delivery of a problem gambling treatment service in a metropolitan area in England, where the concentration of problem gambling is often higher than the national average. Study design: This is a cross-sectional study, using purposively sampled 'experts' and stakeholders involved in the conception and set-up of the service. Methods: Individual semistructured interviews were used to ascertain the depth of information required to fully appreciate the nuances and complexities of the service. Eight participants took part in the interviews, with an additional respondent providing written comments in relation to the interview schedule as a workaround to accommodate the organisational impacts of COVID-19. Results: The article identifies several factors contributing to the successful delivery of the service. Well-managed collaborative provision with expertise from across sectors is critical, but this needs to be balanced against the challenges faced by bridging cultural variances in practice and language. Adopting evidence-based models of delivery was central to practice, and moreover, geographical location is a key consideration to encourage access for those facing gambling problems and discourage feelings of stigma. Conclusions: This article offers a unique contribution to understanding more about the provision of gambling treatment services. This is crucial, given that a greater number of people face challenges as a consequence of gambling harms, and such services should be seen part of forming a coherent public health response.